Female service users’ experiences of secure care in the UK: a synthesis of qualitative research - Ratcliffe, Joanne Marie (The journal of forensic psychiatry & psychology, 2021)
The forensic care needs of females have received increased attention over recent years, with Department of Health (DOH) initiatives highlighting the need for gender-sensitive service provision. However, little is understood about how women experience such services. This review aimed to systematically review and synthesise the findings of existing qualitative literature exploring female service users’ experiences of secure care in the UK. A systematic search of four databases and subsequently applied inclusion and exclusion criteria resulted in fifteen papers that have qualitatively explored female service users’ views on secure care provision. The methodological quality of each paper was appraised before employing a Thematic Synthesis approach to integrate the findings. The resultant papers were appraised to be of varying quality although it was often unclear whether this was due to differing methodological rigour or the reporting of such. The synthesis revealed three overarching themes: ‘Safety and Containment’, ‘Empowerment and Acceptance’ and ‘Making Change’. The findings provide a valuable synthesis of a limited area of qualitative research and highlight areas of importance for female forensic service users. They fall in line with current guidance, as well as indicating new areas for service improvement to ensure positive experiences and outcomes.